The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1088/0004-637x/721/1/686
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Gas and Dust in the Taurus Molecular Cloud

Abstract: We report a study of the relation between dust and gas over a 100 deg 2 area in the Taurus molecular cloud. We compare the H 2 column density derived from dust extinction with the CO column density derived from the 12 CO and 13 CO J = 1 → 0 lines. We derive the visual extinction from reddening determined from 2MASS data. The comparison is done at an angular size of 200 ′′ , corresponding to 0.14 pc at a distance of 140 pc. We find that the relation between visual extinction A V and N (CO) is linear between A V… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
341
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(376 citation statements)
references
References 67 publications
31
341
4
Order By: Relevance
“…Our simulation volume is large enough to contain Taurus-like structures. The velocity dispersion at the earlier time shown from our simulation is the closest to what is seen in Taurus, consistent with the view that the Taurus area is still relatively young (e.g., Hartmann et al 2001;Luhman et al 2003Luhman et al , 2007Pineda et al 2010).…”
Section: Analysis Of the Profilessupporting
confidence: 87%
“…Our simulation volume is large enough to contain Taurus-like structures. The velocity dispersion at the earlier time shown from our simulation is the closest to what is seen in Taurus, consistent with the view that the Taurus area is still relatively young (e.g., Hartmann et al 2001;Luhman et al 2003Luhman et al , 2007Pineda et al 2010).…”
Section: Analysis Of the Profilessupporting
confidence: 87%
“…Figure 1(e) shows the excitation temperature map derived from the following equation with the previous assumption (1) and the beam filling factor of one (e.g., Pineda et al 2010;Kong et al 2015) is the peak intensity of 12 CO ( J = 1-0) in units of K from the above fitting, =…”
Section: Herschel Column Density and Dust Temperature Mapsmentioning
confidence: 99%
“…Nevertheless, the X-factor can vary by a factor of ∼100 in different regions, because 12 CO ( J = 1-0) is often optically thick (Lee et al 2014). For example, Pineda et al (2010) measured X-factor ∼(1.6-12) × 10 20 cm −2 K −1 km −1 s in the Taurus molecular cloud, Lee et al (2014) measured X-factor ∼3 × 10 19 cm −2 K −1 km −1 s in the Perseus molecular cloud, and Kong et al (2015) measured X-factor ∼2.53 × 10 20 cm −2 K −1 km −1 s in the southeastern part of the California molecular cloud. These discrepancies are also found in ISM numerical simulations, which show that the X-factor is likely dependent on extinction, volume density, temperature, metallicity, turbulence, star formation feedback, and so on (Shetty et al 2011a(Shetty et al , 2011bLee et al 2014;Clark & Glover 2015).…”
Section: Co-to-h 2 Conversion Factor Across the L 1551 Molecular Cloudmentioning
confidence: 99%
“…We applied the error beam scaling factor recently proposed by Pineda et al (2010), so that the intensities of the CfA and FCRAO surveys of the 12 CO emission line are compatible. The statistical noise per pixel (with pixel size of 0.33 ) of the velocity-integrated intensity maps is about 0.4 K km s −1 for the 13 CO line.…”
Section: Ancillary Datamentioning
confidence: 99%
“…The column density can also be traced from the nearinfrared (NIR) extinction using the 2MASS point source catalogue (e.g., Dobashi et al 2005;Pineda et al 2010). For comparison with HFI data, we used the extinction map of the central part of the Taurus molecular cloud recently created by Pineda et al (2010) and shown in Fig.…”
Section: Ancillary Datamentioning
confidence: 99%